Study on Medicinal Forest Plants in Ifo, Ogun State, Nigeria, and Factors Shaping Usage Patterns - Abiodun Olusesi Oso; Orimoloye Ipoola Faleyimu; Waheed Akanni Salami; Elizabeth Philip; Rilwan Oluyinka Adewale; Musifat Abosede Kolapo (Jurnal Ilmiah Pertanian)
The utilization of medicinal plants in Nigeria is not solely associated with availability and accessibility but also reflects cultural heritage and local knowledge regarding natural resources. This research addresses the pressing issue of the medicinal utilization of selected forest plants in the Ifo Local Government Area of Ogun State, Nigeria. Commencing with a succinct presentation of the identified problem, the study aims to explore solutions to formulated research questions and test hypotheses at a significance level of 0.05 alpha. Employing a descriptive survey research design, the study involves one hundred respondents randomly selected from Ifo Local Government Area. Five communities, i.e., Alagbole, Lambe, Ibogun, Onihale, and Igbusi, were purposively sampled, with 20 randomly chosen respondents. Data collection utilized a self-structured questionnaire to gather pertinent responses on the variables central to the study. Analysis methods included simple percentages, tables, Pearson Product-Moment Correlation Coefficient (PPMCC), and independent Student's T-test statistic. The research findings highlight, among other insights, the frequent use of forest plant-derived herbs for treating or preventing various health issues in the study area. As a recommendation, the study suggests the need for effective legislation to regulate the harvesting and trade of medicinal plants.